Contribution to Clostridium Difficile Transmission of Symptomatic Patients With Toxigenic Strains Who Are Fecal Toxin Negative. (3rd February 2017) - Mawer, Damian P. C.; Eyre, David W.; Griffiths, David; Fawley, Warren N.; Martin, Jessica S. H.; Quan, T. Phuong; Peto, Timothy E. A.; Crook, Derrick W.; Walker, A. Sarah; Wilcox, Mark H.
Summary: Using whole-genome sequencing, in 2 UK hospitals, patients with diarrhea and toxigenic Clostridium difficile infection, but a negative fecal toxin result, were potential sources for 3% of infections; toxin-positive cases were potential sources for 10%, and another 6% were linked to both groups. Abstract: Background: The role of symptomatic patients who are toxigenic strain positive (TS + ) but fecal toxin negative (FT – ) in transmission of Clostridium difficile is currently unknown. Methods: We investigated the contribution of symptomatic TS + /FT – and TS + /FT + patients in C. difficile transmission in 2 UK regions. From 2-step testing, all glutamate dehydrogenase (GDH)–positive specimens, regardless of fecal toxin result, from Oxford (April 2012 through April 2013) and Leeds (July 2012 through April 2013) microbiology laboratories underwent culture and whole-genome sequencing (WGS), using WGS to identify toxigenic strains. Plausible sources for each TS + /FT + case, including TS + /FT – and TS + /FT + patients, were determined using WGS, with and without hospital admission data. Results: A total of 1447 of 12772 (11%) fecal samples were GDH positive, 866 of 1447 (60%) contained toxigenic C. difficile, and fecal toxin was detected in 511 of 866 (59%), representing 235 Leeds and 191 Oxford TS + /FT + cases. TS + /FT + cases were 3 times more likely to be plausibly acquired from a previous TS + /FT + case than a TS + /FT – patient. Fifty-one of 265 (19%) TS + /FT + cases diagnosed >3 months into the study were genetically related (≤2 single-nucleotide polymorphisms) to ≥1 previous TS + /FT + case or TS + /FT – patient: 27 (10%) to only TS + /FT + cases, 9 (3%) to only TS + /FT – patients, and 15 (6%) to both. Only 10 of 265 (4%) were genetically related to a previous TS + /FT + or TS + /FT – patient and shared the same ward simultaneously or within 28 days. Conclusions: Symptomatic TS + /FT – patients were a source of C. difficile transmission, although they accounted for less onward transmission than TS + /FT + cases. Although transmission from symptomatic patients with either fecal toxin status accounted for a low overall proportion of new cases, both groups should be infection control targets.